Ecological prospective memory assessment in children with acquired brain injury using the Children's Cooking Task. (2nd January 2017) - Krasny-Pacini, Agata; Servant, Violette; Alzieu, Christine; Chevignard, Mathilde
Abstract: Prospective memory (PM) has been shown to be impaired in children with acquired brain injuries (ABI) and is a major concern for parents. Few studies have addressed this issue and most used tasks that are not ecologically valid. The aims of this study were (1) to explore if children who have sustained an ABI suffer PM impairment, measured both by the Children's Cooking task (CCT) PM score and using the 2 PM subtests of the Rivermead Behavioral Memory Test (RBMT), and (2) to explore if the CCT PM score is sensitive to developmental changes in PM in typically developing children and in children with ABI. Fifty-four children with ABI and 33 typically developing controls participated in the study. Children with ABI had significantly lower PM scores and poorer performance in the CCT than their typically developing peers. PM scores increased significantly with age, indicating developmental progress of PM performance.